Alanine Represses γ-Aminobutyric Acid Utilization and Induces Alanine Transaminase Required for Mitochondrial Function in Saccharomyces cerevisiae - Márquez, Dariel; Escalera-Fanjul, Ximena; el Hafidi, Mohammed; Aguirre-López, Beatriz; Riego-Ruiz, Lina; González, Alicia (Frontiers in Microbiology, 2021)
The γ-aminobutyric acid (GABA) shunt constitutes a conserved metabolic route generating nicotinamide adenine dinucleotide phosphate (NADPH) and regulating stress response in most organisms. Here we show that in the presence of GABA, Saccharomyces cerevisiae produces glutamate and alanine through the irreversible action of Uga1 transaminase. Alanine induces expression of alanine transaminase (ALT1) gene. In an alt1Δ mutant grown on GABA, alanine accumulation leads to repression of the GAD1, UGA1, and UGA2 genes, involved in the GABA shunt, which could result in growth impairment. Induced ALT1 expression and negative modulation of the GABA shunt by alanine constitute a novel regulatory circuit controlling both alanine biosynthesis and catabolism. Consistent with this, the GABA shunt and the production of NADPH are repressed in a wild-type strain grown in alanine, as compared to those detected in the wild-type strain grown on GABA. We also show that heat shock induces alanine biosynthesis and ALT1, UGA1, UGA2, and GAD1 gene expression, whereas an uga1Δ mutant shows heat sensitivity and reduced NADPH pools, as compared with those observed in the wild-type strain. Additionally, an alt1Δ mutant shows an unexpected alanine-independent phenotype, displaying null expression of mitochondrial COX2, COX3, and ATP6 genes and a notable decrease in mitochondrial/nuclear DNA ratio, as compared to a wild-type strain, which results in a petite phenotype. Our results uncover a new negative role of alanine in stress defense, repressing the transcription of the GABA shunt genes, and support a novel Alt1 moonlighting function related to the maintenance of mitochondrial DNA integrity and mitochondrial gene expression.